Repotenciación Urbano – Arquitectónica en la Plaza 12 de noviembre en el Cantón San Pedro de Pelileo, Provincia de Tungurahua - Shaina Vanessa Cuenca Cayo (2024)
The urban-architectural repowering of the 12 de Noviembre square in San Pedro de Pelileo, Tungurahua Province, is proposed in order to establish an effective connection between public spaces and commerce of the site. Currently, the canton faces an underutilization of public areas, which limits the realization of diverse activities. The proposed intervention seeks to resolve this deficiency by reconfiguring the plaza, providing a multifunctional space that not only serves commercial needs, but also encourages participation and social gatherings. In the conception of the project, the main elements of connection with the immediate surroundings are used, such as the primary and secondary accesses to the site, nodes, and the demarcation of a central axis. A special hierarchy is given to the main axis, which connects the two squares, thus generating a linear circulation that especially benefits the stores. The design includes the planning of accesses to the site by means of pedestrian walkways to facilitate user mobility. These spaces are planned to promote multifunctionality within the environment, thus contributing to a more dynamic and versatile experience in the area